2018
DOI: 10.3389/fendo.2018.00446
|View full text |Cite
|
Sign up to set email alerts
|

Metformin, an Anti-diabetic Drug to Target Leukemia

Abstract: Metformin, a widely used anti-diabetic molecule, has attracted a strong interest in the last 10 years as a possible new anti-cancer molecule. Metformin acts by interfering with mitochondrial respiration, leading to an activation of the AMPK tumor-suppressive pathway to promote catabolic-energy saving reactions and block anabolic ones that are associated with abnormal cell proliferation. Metformin also acts at the organism level. In type 2 diabetes patients, metformin reduces hyperglycemia and increases insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 127 publications
3
37
0
Order By: Relevance
“…These data are consistent with previous reports from the CCSS and the Bone Marrow Transplant Survivor Study. 33,34 Early reports from the NCT03118128 study have demonstrated that among patients with ALL who express high levels of the ABCB1 gene, those who receive metformin in combination with conventional chemotherapy had higher survival compared with those who Cancer February 15, 2020 only received conventional chemotherapy (83.33% vs 26.47%; P = .025). 6 This increased risk was associated with receipt of total body irradiation in both the CCSS (OR, 12.6; 95% CI, 6.2-25.3) and the Bone Marrow Transplant Survivor Study (OR, 3.42; 95% CI, 1.55-7.52) cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are consistent with previous reports from the CCSS and the Bone Marrow Transplant Survivor Study. 33,34 Early reports from the NCT03118128 study have demonstrated that among patients with ALL who express high levels of the ABCB1 gene, those who receive metformin in combination with conventional chemotherapy had higher survival compared with those who Cancer February 15, 2020 only received conventional chemotherapy (83.33% vs 26.47%; P = .025). 6 This increased risk was associated with receipt of total body irradiation in both the CCSS (OR, 12.6; 95% CI, 6.2-25.3) and the Bone Marrow Transplant Survivor Study (OR, 3.42; 95% CI, 1.55-7.52) cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Several ongoing clinical trials currently are investigating the clinical and biological effects (antitumor) of metformin within the setting of high-risk and refractory and/or recurrent ALL (ClinicalTrials.gov identifiers NCT01324180 and NCT03118128). 33,34 Early reports from the NCT03118128 study have demonstrated that among patients with ALL who express high levels of the ABCB1 gene, those who receive metformin in combination with conventional chemotherapy had higher survival compared with those who Cancer February 15, 2020 only received conventional chemotherapy (83.33% vs 26.47%; P = .025). 33 These studies are relevant because they may provide safety data for the potential administration of metformin in children with ALL during therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Since upstream AMPK activator liver kinase B1 (LKB1) is known to act as potent tumor suppressor, possible link between metformin administration and reduced cancer incidence has been suggested and indeed proven by the first epidemiological study . Since then, anticancer effect of metformin has been demonstrated in various models in vivo as well as in vitro …”
Section: Introductionmentioning
confidence: 99%
“…5 Since then, anticancer effect of metformin has been demonstrated in various models in vivo as well as in vitro. 6,7 Although metformin belongs to widely prescribed drugs, its mechanism of action in both type II diabetes and cancer is still under investigation. Based on epidemiological studies, association between adiposity and increased risk of cancer has been proposed via deregulation of key pathways including insulin resistance, but the direct connection is missing.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the molecular mechanisms of death induction by metformin are believed to be via endoplasmic reticulum stress, the antidiabetic drug is another chemotherapeutic capable of inhibiting the ETC and the TCA cycle 95 . In a mouse model of PTEN ‐deficient T‐ALL, metformin inhibits leukemia progression and synergizes with 2‐DG 96,97 . A combination of metformin with anthracyclins and daunorubicin in cALL cell lines and patient samples also shows synergistic effect in vitro 98 .…”
Section: Cell Metabolism In Callmentioning
confidence: 99%